Explain the Experience of Family Caregivers Regarding Care of Alzheimer's Patients: A Qualitative Study - Ashrafizadeh, Hadis; Gheibizadeh, Mahin; Rassouli, Maryam; Hajibabaee, Fatemeh; Rostami, Shahnaz (Frontiers in Psychology, 2021)
Introduction: Due to the long-term and progressive nature of Alzheimer's disease, these patients need caregivers who will be responsible for their long-term care and who may then experience an increasing burden related to the progressive disease course, so it is important to understand the experiences of caregivers. The aim of this study was to explain the experience of family caregivers regarding care of Alzheimer's patients. Methods: The present qualitative study employed a conventional content analysis approach and was conducted in Iran in 2020. This research was done through in-depth and semi-structured interviews with 11 qualified caregivers enrolled in a purposive sampling method. Interviews continued until data saturation. Data analysis was performed simultaneously with data collection. Interviews were recorded, transcribed and analyzed through Graneheim and Lundman style content analysis and data management was done with MAXQDA software. In order to achieve the accuracy and validity of the study, the Four-Dimensions Criteria (FDC) by Lincoln and Guba, credibility, dependability, confirmability, and transformability were considered and used. Results: A total of 11 caregivers with mean age and standard deviation 48, ±26.12 participated in the study. The acquired data were put in two main categories of “burnout and exhaustion” with six subcategories and “excellence and personal growth” with three subcategories. Conclusion: In this study, we found that perceptions of caregivers' role were not the same among study participants, who experienced both positive and negative dimensions of care provision to AD patients. The care experience has a spectrum that, in some people, leads to positive outcomes such as growth. A major part of caregiver challenges is related to the burden of caregiving strain and the erosive nature of the disease. Therefore, health planners should identify the challenges, pain and suffering of caregivers and seek to address them through appropriate strategies.